Exploration of Mathematical Concepts in the Katto-Katto Game - Irmayanti Irmayanti; Hikrawati Hikrawati (Advanced Journal of STEM Education, 2023)
One game that is currently viral in Sinjai Regency and even throughout Indonesia is the Katto-Katto game. Games that can distract children from online games. In addition, this game is often contested at schools and in the community, especially in Sinjai District. This research is expected to be able to provide information to teachers and students about the mathematical concepts contained in the katto-katto game. This game is not just played but the teacher must be able to integrate it with learning in the classroom. The type of research in this study is an exploration with a qualitative approach. The subjects of the study were primary school children and teachers in the Sinjai district. The technique of taking the subject is purposive sampling. The data collection technique used was observation, interviews to find out the mathematical concepts of the game tools, and documentation to document the shape of the katto-katto game tools. The instruments used were observation, interview guides, and documentation. The analytical techniques used are reduction, data display, and concluding. Data were analyzed by triangulation of methods and sources. From the results, it can be concluded that the katto-katto game contains several mathematical concepts that are taught in schools both in terms of tools and the process of playing. In terms of the tool, there is a spatial concept in the form of a ball, the measurement is on the rope. In the game process, there are concepts of weight measurement, calculation, the angle formed, and speed.